Microsoft office 97 - Warner, Nancy D. (Que, 1998)
The book guide to use each of the following software appications: Word, Excel, Powerpoint, Outlook, and apply to other applications. For example, the formatting features in Word will apply to formatting text in Excel, Powerpoint, and in many cases even Outlook